Transformational Digital Leadership And Public Legitimacy: Purwakarta Community Perceptions Of Dedi Mulyadi - Nur Fitriyani; Mega Zhafarina Purwono (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study examines Dedi Mulyadi transformational digital leadership patterns and the construction of Purwakarta societys perceptions of the phenomenon of person centered leadership based on social media. The approach use a qualitative descriptive with netnography methods supported by indepth interviews with three (3) informants. Methodologically, this study operationalizes four (4) core stages of Kozinets netnography framework introspection, digital ecosystem mapping, interaction archiving, and theory based interpretation to rigorously link empirical data with the research objectives. The result is Dedi Mulyadi legitimacys is maintained through consistent humanistic content and direct engagement across digital platforms with a total of more than 34 million followers, effectively extending leadership influence beyond formal office boundaries. In terms of quantitative data, at the cross platform sentiment analysis reveals a dominance of positive sentiment at approximately 59% standing in stark contrast to the 22% of critical sentiment centered on concerns regarding excessive digital exposure and rather superficial content. Then the public perceives a contrast between the leaders rapid personal movements on social media and formal bureaucratic mechanisms, which have the potential to create figure dependency and weaken institutional trust. This research contributes to the development of an adaptive public sector leadership model in the digital era. Research shows that the success of transformational digital leadership in building public image and legitimacy needs to be balance with strengthen the capacity of the formal bureaucracy so that public trust does not only rest on the figure of the leader, but also on the sustainability of the government system.